Perilaku Sadar Sampah di SD Negeri 2 Kelusa Gianyar - Ni Luh Putu Ening Permini; I Dewa Gede Putra Sedana; I Dewa Agung Ayu Eka Idayanti; I Ketut Witarka Yudiata; Ni Luh Nita Pitriyanti; Si Luh Ayu Made Widnyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Clean living behavior can be done by maintaining the sustainability of life can be done by reducing waste, saving energy, planting trees, and not littering. Waste sorting can be done by separating organic and inorganic waste into different trash bins. In addition, inorganic waste can also be separated again based on its type, such as plastic, paper, glass, and metal. Facilitates the process of collecting and processing waste for recycling. The Principles of Clean and Healthy Living Behavior (PHBS) recommend the use of waste sorting methods. The daily habits that we do to maintain personal and environmental cleanliness consist of this behavior. . Along with the emergence of various diseases that often attack children aged 6-12 years, PHBS in schools is a collection of behaviors carried out by students, teachers, and school residents based on learning so that they are able to independently prevent disease, improve their health. Implementation of better waste sorting practices can reduce the negative impact of waste on the environment, increase the efficiency of waste management, and provide long-term benefits for school residents. Schools are one of the places that have great potential to educate students about good waste management. SD Negeri 2 Kelusa has problems related to the lack of student knowledge about waste sorting and utilization, especially organic waste. Most students at SD Negeri 2 Kelusa still have limited understanding of the types of waste and how to process it. Most students do not realize and understand that organic waste can be reused, so they tend to throw it away with other waste.